Panel data analysis using a production model for education an aid to determining the national budget of Philippine state universities and colleges - Doloroso, Sigfred M. (2007)
This paper showcases the relationship of budget and quality of public higher education institution. The idea is to determine an alternative way of computing the budget of State Universities and Colleges and at the same time producing quality education. Furthermore, it is crucial to investigate the need for, or, alternatively, the support for laws and collective agreement on funding higher education. This study uses a panel data set of State Universities and Colleges covering the period of 1999-2006 to determine possible alternative weights for the Normative Financing Scheme. The data includes detailed information on 109 SUCs over 8 years totaling 872 observations.
Vita.
Thesis (M.Statistics)--University of the Philippines Diliman.
Keywords: State universities and colleges -- Philippines; State universities and colleges -- Philippines -- Finance; Universities and colleges -- Law and legislation -- Philippines; Financial analysis